Model Pembelajaran Kooperatif Tipe Jigsaw dan Numbered Head Together Dilihat dari Hasil Belajar Matematika Siswa Pada Materi Persamaan Garis Lurus - Nurjannah Nurjannah; Ketut Sarjana; Baidowi Baidowi; Nurul Hikmah (Pendidikan Matematika FKIP Universitas Mataram, 2021)
This research aims to (1) know the results of learning mathematics students who use the Jigsaw cooperative learning model (2) know the results of learning mathematics students who use a cooperative learning model NHT type (Numbered Head Together) (3) find out whether there are differences in students' mathematics learning outcomes using the Jigsaw type cooperative learning model, with the type of NHT on the straight-line equation material.This type of research is an experimental Quasi with Post test Only Control Group Design. The sample class was selected using the random sampling cluster technique, so class VIII B was obtained as an experimental class with the Jigsaw model and VIII C as an experimental class with the NHT model. The data retrieval in this study was taken by giving a post test on the research subject. Analysis of test data was using two-of-pooled variance test-t independent samples. Based on the results of the data analysis obtained there was no significant difference in mathematical learning outcomes between classes that were taught with the type Cooperative learning model of Jigsaw and NHT. It can be seen from the hypothesis testing using a test-T pooled variance at a significant level of 5%, indicating that the t_count i.e. 0.80 was smaller than the t_table i.e. 1.67.